2014
DOI: 10.1136/bjsports-2014-093494.10
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between 2d Knee Valgus Angle During Single Leg Squat (Sls), Single Leg Landing (Sll), and Forward Running

Abstract: Background: Two-dimensional (2D) analysis of knee valgus during common athletic screening tasks such as SLS has been purported to identify individuals who may be at a high-risk of ACL injury. There is limited literature exploring the relationships between joint motion during SLS and other athletic tasks associated with knee joint injuries, in order to evaluate the effectiveness of the SLS to identify athletes with hazardous knee motion in a range of athletic tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our results showed a strong relationship between FPPA in the SLS and SLL (r = 0.52) and moderate relationship between the SLS and DJ (r = 0.30). The relationship between SLS and SLL supports the findings of the preliminary study on by Atkin et al [15] , albeit the strength of the correlation is weaker in the current study. Atkin et al only studied eight women and therefore the stronger correlations may not represent those of the larger population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results showed a strong relationship between FPPA in the SLS and SLL (r = 0.52) and moderate relationship between the SLS and DJ (r = 0.30). The relationship between SLS and SLL supports the findings of the preliminary study on by Atkin et al [15] , albeit the strength of the correlation is weaker in the current study. Atkin et al only studied eight women and therefore the stronger correlations may not represent those of the larger population.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, Atkin et al [15] have shown a relationship in women between 2D FPPA in the SLS and running which demonstrates the potential clinical utility of 2D FPPA to screen female athletes using a simple SLS test.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For maximum knee abduction angles, maximum hip adduction angles, and maximum external knee abduction moments, most significant correlations were observed between the two landings and between the single-leg squat and landings. Atkin et al (2014) identified a moderated correlation for 2D knee abduction angles between a single-leg landing and a single-leg squat. Wallace et al (2008) found mostly small correlations for 3D knee abduction and hip adduction between a double-leg landing and a double-leg squat.…”
Section: Discussionmentioning
confidence: 94%
“…Based on previous studies (Atkin et al, 2014;Butler et al, 2012;Earl et al, 2007;Stensrud et al, 2011;Wang, 2011;Yeow et al, 2010Yeow et al, , 2011, a mediumto-large effect size was expected for the differences and correlations in kinematic and kinetic variables during landing and squat tasks. Assuming a Cohen's f of 0.25 for analysis of variance (ANOVA), a sample size of 24 was needed for a Type I error at the level of 0.05 to achieve a power of 0.8.…”
Section: Participantsmentioning
confidence: 98%